Territorial Social and Economic Disparities Within the Development of Arad County - Irena Mocanu (Human Geographies: Journal of Studies and Research in Human Geography, 2008)
Identifying the territorial disparities in the socio-economic development of Arad County implies taking the following six research stages: selecting the relevant statistical indicators, analysing their socio-economic significance, standardising the absolute values of the indicators, calculating the Complex Index of Development, delimitating and generally characterising both the favourable areas for development and the less favourable ones. The indicators were selected to reflect the specifics of agricultural, industrial and touristic activities, of the health and education systems, of the dwellings and public utility infrastructure, of the labour and inhabiting force. The territorial distribution of the value of the 24 indicators and secondary indexes emphasised in most cases a difference between the ATU (administrative territorial units) from the Eastern and Western parts of the Arad County. The Complex Index of Development (calculated as Hull Score) offered the possibility of separating the areas that were favourable for socio-economic development (generated by the urban areas along two longitudinal lineaments, e.g. Western and Central, and in the irregular areas in the Carpathian depression) from the less favourable areas (62% of the ATU in the Arad County).